Taman Baca Masyarakat Iqra Aksara Lampung Sebagai Upaya Pelestarian Budaya Lampung Di Daerah Way lima Pesawaran - Jovanda, Renaldy; Fradila, Renata; Aditia, Dimas; Sumargono, Sumargono (Universitas Negeri Padang, 2021)
The Iqra Aksara Community Reading Garden Program as a medium in the teaching and learning process that is applicative is expected to foster student interest and motivation in learning the Lampung language. One of the factors that affect the quality of education is the presentation of creative and innovative learning materials. Related to this, it is necessary to have learning media that can attract students' interest in learning. Besides the media, creative teachers are also needed who have expertise in the field of information technology and computers, so it is important to carry out socialization that contains education and inculcation of community-based cultural values. This activity is carried out with the hope that students can make the best use of it, as well as the hope that in the future it will bring up local communities who are more loyal to contribute to continue to spread the teaching of the Lampung language among the younger generation. Based on the existing problems related to the urgency of the Lampung language in this increasingly unstoppable era of globalization, it is necessary to make a new breakthrough in the field of social services intended for students in learning the Lampung language.